Few-Shot Learning Meets Transformer: Unified Query-Support Transformers for Few-Shot Classification - Wang, Xixi; Wang, Xiao; Jiang, Bo; Luo, Bin (IEEE transactions on circuits and systems for video technology, 2023)
The goal of Few-shot classification (FSL) is to identify unseen classes with very limited samples has attracted more and more attention. Usually, it is formulated as a metric learning problem. The core issue of few-shot classification is how to learn (1) consistent representations for images in both support and query sets and (2) effective metric learning for images between support and query sets. In this paper, we show that the two challenges can be well modeled simultaneously via a unified Query-Support TransFormer (QSFormer) model. To be specific, the proposed QSFormer involves global query-support sample Transformer (sampleFormer) branch and local patch Transformer (patchFormer) learning branch. sampleFormer aims to capture the dependence of samples in support and query sets for image representation. It adopts the Encoder, QS-Decoder and Cross-Attention to respectively model the Support, Query (image) representation and Metric learning for few-shot classification task. Also, as a complementary to global learning branch, we adopt a local patch Transformer to extract structural representation for each image sample by capturing the long-range dependence of local image patches. In addition, we introduce a novel Cross-scale Interactive Feature Extractor (CIFE) to extract and fuse different scale CNN features as an effective backbone module for the proposed few-shot learning method. We integrate these into a unified framework and train it in an end-to-end way. A large number of experiments are conducted on four popular datasets to validate the superiority and effectiveness of the proposed QSFormer.